2020
DOI: 10.1155/2020/7437892
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic Diabetic Ketoacidosis in a Lung Cancer Patient Using Empagliflozin

Abstract: Diabetic ketoacidosis is a leading cause of morbidity and mortality in diabetic patients, and its diagnosis should be timely and accurate. SGLT2 inhibitors are a new class of antidiabetic medications that increase the renal excretion of glucose. It is thought that increased urinary excretion of glucose will mask hyperglycemia during DKA. This can lead to a delayed diagnosis of DKA and worsen outcomes. In this report, we detail a case of euglycemic DKA in a patient who presented to the Emergency Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Five studies mentioned the need for human immunodeficiency virus testing [ 25 , 37 , 39 , 42 , 53 ]. Procalcitonin was tested in 10/89 (11%) studies as a marker suggestive of bacterial sepsis, although it cannot help to localize the site of infection [ 18 , 30 , 34 , 38 , 41 , 52 , 62 , 65 , 66 , 75 ]. Bone marrow examination and biopsy of lesions or lymph nodes were used to rule out malignancy or HLH [ 41 , 44 – 46 , 50 – 53 , 62 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies mentioned the need for human immunodeficiency virus testing [ 25 , 37 , 39 , 42 , 53 ]. Procalcitonin was tested in 10/89 (11%) studies as a marker suggestive of bacterial sepsis, although it cannot help to localize the site of infection [ 18 , 30 , 34 , 38 , 41 , 52 , 62 , 65 , 66 , 75 ]. Bone marrow examination and biopsy of lesions or lymph nodes were used to rule out malignancy or HLH [ 41 , 44 – 46 , 50 – 53 , 62 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the universal absence of history as a component of the diagnostic criteria for SUO (when provided), 30/89 (34%) of studies discussed the merits of specific, focused history taking. Most of these studies describe how a particular aspect of history helped direct further investigations to confirm the infective source or to suggest alternative diagnoses [34][35][36][37][38][39][40]. Important aspects of history taking included travel history which may reveal exposure to endemic pathogens, such as malaria and rickettsia [34,37].…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…e mechanism of action of SGLT2i is independent of insulin and can be used at any stage of illness in T2DM, and in addition to promoting normoglycaemia, they have favourable effects in reducing body weight, blood pressure, Case Reports in Endocrinology reducing atherosclerotic cardiovascular events in patients with established cardiovascular disease, reducing heart failure hospitalisation rates and progression of renal disease [6,7]. Euglycemic acidosis occurring in the context of SGLT2i use in patients with malignancy is scarce, with previous reports documenting its incidence in the case of colorectal cancer [8], pancreatic cancer [9], and lung cancer [10]. Although previous data have demonstrated that SGLT2i-associated euglycemic ketoacidosis is not associated with any particular demographic or comorbid population, perhaps further prospective studies are required to determine whether malignancy can further predispose to the development of euglycemic ketoacidosis and, additionally, whether certain malignancies are associated with an increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Euglycemic acidosis occurring in the context of SGLT2i use in patients with malignancy is scarce, with previous reports documenting its incidence in the case of colorectal cancer [ 8 ], pancreatic cancer [ 9 ], and lung cancer [ 10 ]. Although previous data have demonstrated that SGLT2i-associated euglycemic ketoacidosis is not associated with any particular demographic or comorbid population, perhaps further prospective studies are required to determine whether malignancy can further predispose to the development of euglycemic ketoacidosis and, additionally, whether certain malignancies are associated with an increased risk.…”
Section: Discussionmentioning
confidence: 99%